Self-assembly of all-conjugated block copolymer nanoparticles with tailoring size and fluorescence for live cell imaging. Issue 48 (22nd November 2016) - Jiao, Hui-Feng; Wang, Xiaofeng; Yao, Kai; Chen, Peng; Jia, Zhenrong; Peng, Zhiping; Li, Fan
Abstract : Here, we describe aqueous nanoassemblies of rod–rod diblock polythiophene into core–shell nanospheres. Benefitting from their good photostability and low cytotoxicity, the nanoparticles meet the crucial requirements for cellular imaging and other biological applications. Abstract : A series of all-conjugated polythiophene diblock copolymers containing hydrophobic (hexyl) and hydrophilic (triethylene glycol) side chains were synthesized via a nickel-catalyzed quasi-living polymerization. The correlations between block ratios and the self-assembled nanostructures of the block copolymers in thin films and in various solutions were examined. The copolymers dispersed in water via a slow dialysis method produced molecular-level self-assembled core–shell nanospheres with a crystallized hydrophobic core and a hydrophilic amorphous shell, which was proved by TEM images. The size and quantum yield of polymer micelles could be easily tuned via the block ratio of copolymers. The resulting core–shell nanospheres of BP40 composed of 40 mol% P3HT blocks with an average size of 120 nm exhibit high quantum yield (19% in aqueous medium), good photostability and low cytotoxicity. Utilized as a far-red/near-infrared (FR/NIR) cellular probe, BP40 is internalized efficiently by the cells and accumulated in the cytoplasm to give bright fluorescence.